Social interaction anxiety and personality traits predicting engagement in risky sexual behavior - Rahm-Knigge, Ryan L., author; Conner, Bradley T., advisor; Steger, Michael F., committee member; Luong, Gloria, committee member (Colorado State University. Libraries, 2017)
Social anxiety disorder is a prevalent psychiatric condition, especially among adolescents (American Psychiatric Association, 2013, p. 204). Individuals with social interaction anxiety, which pertains to interpersonal exchanges with others, ruminate on perceived failures in past interactions, withdraw from or avoid social encounters, and engage in coping behaviors in response to negative feelings (Clark & Wells, 1995; Hoffman, 2007; Kashdan, 2004; Leary, 2001). While the majority of individuals with social interaction anxiety avoid risky situations, a subset engages in risky behaviors, including more frequent sexual encounters and unprotected sex (Kashdan, Elhai, & Breen, 2008; Kashdan & Hoffman, 2008; Kashdan, McKnight, Richey, & Hoffman, 2009). The personality constructs sensation seeking, emotion dysregulation, and impulsivity predict engagement in risky sexual behavior and have been suggested in previous studies to explain the relation between social interaction anxiety and risky sexual behavior (Arnold, Fletcher, & Farrow, 2002; Gullette & Lyons, 2005, 2006; Hoyle, Fejfar, & Miller, 2000; Kalichman et al., 1994; Kashdan et al., 2008; Kashdan et al., 2009; Kashdan & Hoffman, 2008; Kashdan & McKnight, 2010; Parent & Newman, 1999). Therefore, the present study hypothesized that latent classes of social interaction anxiety and personality traits would be identified that distinguish engagement in risky sexual behaviors. Finite mixture modeling was used to discern latent heterogeneous classes of social interaction anxiety and facets of sensation seeking, emotion dysregulation, impulsivity, behavioral approach, and behavioral inhibition. Risky sexual behaviors were treated as auxiliary variables. Four classes were discerned: two low social interaction anxiety classes distinguished by facets of emotion dysregulation, positive urgency, and negative urgency (Low SIAS High Urgency and Low SIAS Low Urgency) and two high social interaction anxiety classes distinguished by positive urgency, negative urgency, risk seeking, and facets of emotion dysregulation (High SIAS High Urgency and High SIAS Low Urgency). Of importance to this study were the findings that the High SIAS High Urgency class was significantly more likely to engage in all identified risky sexual behaviors than the High SIAS Low Urgency class and that the High SIAS High Urgency class did not significantly differ from the Low SIAS High Urgency and Low SIAS Low Urgency classes in engagement in risky sexual behaviors. This study extends previous findings on the heterogeneity of social interaction anxiety by identifying the effects of social interaction anxiety and personality on engagement in risky sexual behaviors.